Paratextual Manipulations of Persian into English Translations of Political Texts: The Case of MEMRI ‎from Narrative Theory Perspective‎ - Alibabaee, Ahmad; Shokohipoor, Narges (Iranian Journal of Translation Studies, 2016)
Conflict time periods take studies on political text translation to the forefront of translation studies. ‎Assuming that each party in a conflict may attempt to maintain its interest, this study aimed to ‎identify the translation devices commonly used to reframe and disseminate desired narratives by ‎MEMRI (Middle East Media Research Institute). To investigate whether such devices are used in ‎MEMRI’s website, 37 dispatches were selected and analyzed based on the narrative theory and ‎the notion of framing. The results showed that MEMRI had used such reframing devises in ‎paratextual levels as title, heading and introduction to reframe the translations in a way to highlight ‎Iranians' hatred and aggression towards Israel. Moreover, there were cases where MEMRI's ‎translations were accompanied by specific images that made the reader doubt the dependability ‎of Iran's claims. It is, thus, concluded that all of these attempts may potentially be due to the ‎MEMRI's predisposition to show Iran as a potential threat for Israel. Several ideas and issues are ‎also discussed to delve into the use of such devises for reframing.‎